Guidelines for Public Participation in Reducing Plastics Use in the Nong Ta Team Subdistrict, Pranburi District, Prachuap Khiri Khan Province - Srithong, Pannita; Adulbutr, Suchart; Maitreesophon, Bampen (Journal of Humanities and Social Sciences Review, 2024)
This mixed-method research aimed to: 1) study the level of public participation in reducing plastics use in the Nong Ta Team Subdistrict, Pranburi District, Prachuap Khiri Khan Province, 2) study a correlation between personal characteristics and public participation in reducing plastics use, 3) study the cause-effect relationship between stimulating factors and public participation in reducing plastics use, and 4) study the guidelines for public participation in reducing plastics use. The sample group consisted of the 400 residents residing in the Nong Ta Taem Sub-district area, Pranburi District, Prachuap Khiri Khan Province, and 9 key informants. Data were analyzed by using frequency, percentage, mean, standard deviation, chi-square, and multiple regression analysis. The research resulted that: 1) the public participation in reducing plastics use was at a high level, 2) the personal characteristics in terms of education, income, and occupation were related with public participation in reducing plastics use on the statistically significant level at 0.05, 0.01, and 0.001, respectively, 3) the stimulating factors on legal measures in terms of perception, and social measures were logically related with the people for reducing the plastics use at the statistically significant level of 0.05 respectively, and 4) the guidelines for public participation in reducing plastics use were revealed that: should make understanding and provide knowledge to the people through various channels and increase public participation in reducing plastics use.